1989
DOI: 10.1152/ajplung.1989.257.6.l393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium deficiency on glutathione-induced protection from hyperbaric hyperoxia in rat

Abstract: Exposure of rats to 100% O2 at high pressure (greater than 2.0 ATA) results in generalized convulsions and death within several hours. The tripeptide, glutathione, has been shown to protect rats exposed to hyperbaric hyperoxia with delayed onset of seizures and prolonged survival. To investigate the hypothesis that glutathione exerts its protective effects via the glutathione redox cycle, we injected selenium-deficient rats and their selenium-supplemented controls with either glutathione (1 mmol/kg) or an equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…The variable outcome of GSH-Px activity is also concordant with literature since having the most conflicting reports above all antioxidant enzymes [32,33,44,45]. In our previous work, we determined GSH-Px activity two times, once with a single session [37] and second with a multiple HBO exposure procedure [38], which resulted both with statistically insignificant levels in brain and lung tissue of rats.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The variable outcome of GSH-Px activity is also concordant with literature since having the most conflicting reports above all antioxidant enzymes [32,33,44,45]. In our previous work, we determined GSH-Px activity two times, once with a single session [37] and second with a multiple HBO exposure procedure [38], which resulted both with statistically insignificant levels in brain and lung tissue of rats.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, the potential risk of toxicity belong to breathed 100% oxygen during treatment sessions restricts further widening of its indication area. The majority of experimental work established on this topic have been tended to direct toxic effects of HBO with relatively higher pressure/duration ranges than clinically used, such as 4-5 ATA and/or longer periods over 2 h [11,13,[32][33][34][35]. It is impossible to adapt these works to approved therapeutic limits, i.e., a maximum exposure pressure of 3 ATA and 2 h duration [1].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, GSH-Px has had the most confl icting reports among all antioxidant enzymes. For example, in contrast to their above summarized work ( 14 ), Jenkinson et al ( 15 ) reported a decreasing effect of GSH-Px with HBO exposure in another study. The results of Puglia and Loeb's ( 23 ) and Pablos et al's ( 21 ) studies presented a similar outcome in rats, whereas two more recent studies performed with humans reported unchanged blood GSH-Px values with one ses- Fig.…”
Section: Discussionmentioning
confidence: 77%
“…For example, Harabin et al ( 12 ) reported GSH-Px to decrease and SOD to increase in the rat lung with the activities of these enzymes not differing in brain tissue. Boadi et al ( 5 ) stated that GSH-Px activity was found to be increased but SOD unchanged in the rat lung and brain, and Jenkinson et al ( 14 ) reported that GSH-Px was not changed in rat lung and brain tissue after HBO exposure. In our previous studies ( 3,20,30 ) as well as in the present one, HBO always tended to have an increasing effect on antioxidant enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the greater the concentration of O 2 in the inspired air, the more extensive is the molecular damage to the organism. This damage becomes readily apparent when animals (or humans) are exposed to 100 % O 2 at increased atmospheric pressure (Jenkinson et al 1989). Given that melatonin neutralizes O 2 -derived reactants, this indole would be expected to protect against hyperbaric hyperoxia exposure.…”
Section: Melatonin : Direct Scavenging Actionsmentioning
confidence: 99%